La satira grottesca nelle tre ‘povesti’ di Michail Bulgakov: la tragica carnevalizzazione della Russia degli anni Venti - Cheti Traini (Between, 2016)
At the end of 1921 Mikhail Bulgakov, a young doctor from Kiev with literary expectations, finally moved to Moscow. The capital of the new Soviet world is entering into the Nep’s years, featured by the figure of a new social climber, the nepman. Moscow and the entire Russia are changing, by staging a kind of huge Carnival of which Bulgakov chooses to portrait its contradictory and paradoxal nature throughout the instruments of a grotesque satire. The writer intends to represent the relativity and absurdity of situations that cross the threshold of reality to penetrate the world of paradox and absurd, where mistaken identities, amazing discoveries and unlikely experiments may be read as dethronizations of inauthentic heroes, unmasking of false myths, tragi-comic teasing of the authoritarian word.